A fuzzy framework for modelling confidence in multi-agent system - Basheer G.S.; Ahmad M.S.; Tang A.Y.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fuzzy logic; Software agents; Certainty; Confidence; Importance of Trust; MAS; Trust; Multi agent systems